2014
DOI: 10.1080/15389588.2014.948615
|View full text |Cite
|
Sign up to set email alerts
|

Work Zone Safety Analysis and Modeling: A State-of-the-Art Review

Abstract: The synthesis of the literature suggests that the presence of a work zone is likely to increase the crash rate. Crashes are not uniformly distributed within work zones and rear-end crashes are the most prevalent type of crashes in work zones. There was no across-the-board agreement among numerous papers reviewed on the relationship between work zone crashes and other factors such as time, weather, victim severity, traffic control devices, and facility types. Moreover, both work zone crash frequency and severit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…In terms of work zone rear-end crashes, a plethora of literature report the observation of an increased rate of rear-end crashes in work zones compared to nonwork zones [5][6][7][8][9]. Qi et al investigated rear-end crashes in the work zones and utilized the ordered probit model.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of work zone rear-end crashes, a plethora of literature report the observation of an increased rate of rear-end crashes in work zones compared to nonwork zones [5][6][7][8][9]. Qi et al investigated rear-end crashes in the work zones and utilized the ordered probit model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, it has been showed that rear-end collisions constitute 30% of all injuries and 29.7% of all property damage in the USA [4]. Additionally, it is also argued that rear-end crashes mostly occur on highway work zones rather than nonwork zones [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The WZ features used for clustering are presented in Table 2. Note that WZ lengths were not available for the 54,000 WZs considered in this study, but since WZ lengths have been shown to influence crash frequency [71], we expect that including this variable in the future would improve the model accuracy. Additionally, a variety of other temporal variables would likely enhance model performance (e.g., speed variance and weather), but these characteristics would be unavailable ahead of time, and the proposed approach focuses on predicting the crash probability at a future work zone.…”
Section: Datamentioning
confidence: 99%
“…Despite many different modeling approaches and perspectives, the majority of literature focuses on either work zones or crash frequency independently, with comparatively little research dedicated to modeling collision frequency/risk based on work zone characteristics. Within this niche body of research, most papers conclude that increased vehicle demand, work zone length, and duration all increase the number of collisions that occur at a work zone over a period of time [71]. However, we are more interested in determining the probability of a collision rather than the number of collisions that occur.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper summarized most of the work in this area dating back to 1978 (Yang et al, 2014). Much of the work in this area has involved estimating the change in crash risk that under work zone operations as compared to "normal" (i.e., non-work zone) traffic operations.…”
Section: Literature Reviewmentioning
confidence: 99%